Effectiveness of kepok banana stem extract (Musa Acuminata) on the immune response of catfish (Clarias gariepinus) infected with Aeromonas hydrophila - Hany Handajani; Anis Zubaidah; Dina Izzah Kamila (Depik, 2024)
Catfish have high economic value, fast growth, and are easy to cultivate. This is the reason why catfish cultivation is increasing. However, there are still obstacles in the cultivation process, namely the threat of disease, one of which is the Motile Aeromonas Septicaemia (MAS) disease caused by Aeromonas hydrophila bacteria. The countermeasure can be done by using active compounds found in plants, including banana stems. This study aimed to determine the effectiveness of giving banana stem extract to carp culture media and treating A. hydrophila disease. This research used an experiment with a completely randomized design. The treatments tested were the addition of banana stem extract at a dose of 5% (treatment A), 10% (treatment B), 15% (treatment C), and antibiotics (treatment K-), and without extract treatment (treatment K+). Each treatment was repeated three times. The results showed that the administration of banana stem extract significantly affected the fish's erythrocytes, leukocytes, and blood glucose. Leukocyte differential observation showed that kepok banana stem extract had a significant effect on eosinophils, lymphocytes, and neutrophils but no significant effect on monocytes. In analyzing fish blood, the optimal values were 7.640.190a cells/mm3 for leukocytes, 3.600.116d cells/mm3 for erythrocytes, 656.028b mg/dl for glucose, 74.670.577d% for lymphocytes, 5.670.577a% for neutrophils, and 00a% for eosinophils. The results indicate that treatment B with 10% kepok banana stem extract was the most effective in administering the extract to catfish infected with A. hydrophila bacteria.Keywords:Dumbo catfishLeukocytesErythrocytesGlucoseMusa AcuminataAeromonas hydrophila